Penyuluhan Program Transmigrasi di Kampung Klagulus Distrit Makbon Kabupaten Sorong - Madaul, Rahful A; Ibal, La; Asriadi (AJAD : Jurnal Pengabdian kepada Masyarakat, 2023)
The location of the counseling is Klagulus Village, Makbon District, Sorong Regency, Southwest Papua Province. Persuasive counseling techniques using lecture methods and outreach regarding transmigration. This activity was carried out at the extension center in Klagulus Village, Makbon District, Sorong Regency, and the number of counseling participants was 46 heads of families representing several settlements. The transmigration counseling participants are community leaders, RW, RT, PKK, and vulnerable poor residents who are the targets of the transmigration program. The method used is descriptive-qualitative. The result of this service is that the delivery of transmigration program counseling material is carried out through three stages, namely socialization, implementation of activities, and program planning. This outreach program is intended to convey to the community the transmigration programs that will be built in Klagulus Village as well as the implementation of transmigration.